Analysis of Entrepreneurial Skills Development through Farm Practical Training Programmes of University of Ibadan and University of Agriculture, Abeokuta. - Ademola A Ladele; O M Agbebaku (Journal of Agricultural Extension, 2006)
Farm Practical Training Programme is an important component of the curricula of many tertiary institutions basically for graduates to gain proficiency in practical agriculture. This paper aims at examining the extent to which the programmes of two universities have met the entrepreneurial skills development goal and the perception ofparticipants on how much the programmes have affected their orientation towards practical agriculture. Using simple random sampling technique, 143 out of 569 students from University of Ibadan and University of Agriculture Abeokuta were used to obtain data. It was found that though, most trainees somehow appreciated the programme, many of them still prefer career in non-agricultural establishments. There was clear indication that studying agriculture does not amount to aspiring towards career in practical agriculture. Hypotheses tested did not show significant difference in the students' perceptions in the two universities at 5% level of significance. There was also no significant relationship between age, sex and respondents' background and their perceptions of the progrmme. However, about 32% would choose career in practical farming, given appropriate motivation and incentives. It is recommended that a special degree programme be mountedfor this cadre oftrainees.